Microstructure, hardness and cavitation erosion resistance of different cold spray coatings on stainless steel 316 for hydropower applications. (December 2020) - Jiang, Xiujuan; Overman, Nicole; Smith, Christopher; Ross, Kenneth
Graphical abstract: Highlights: Cold sprayed Inconel 625, SS316 and NiCr-CrC were investigated. Microstructure and hardness of the cold sprayed and the base metal were evaluated. Cavitation testing was done according to ASTM G134. Cold spray processed Inconel 625 achieved the best cavitation erosion performance. Abstract: There is an urgent need for repair of hydropower components that have undergone damage due to cavitation. This study investigated the relevant properties of different materials using cold spray technology. Stainless steel (SS) 316, Inconel 625 and CrC-NiCr materials were deposited onto base metal SS 316 using cold spray. Cold spray achieved deposits with relatively low porosities, and intimate contact between the deposit and the base metal was observed. Severe plastic deformation was imparted during the cold spray process and nanostructured regions were observed in all three deposits across the interfacial area. Cold sprayed deposits exhibited elevated hardness in contrast to that of the base metal SS 316. The cavitation erosion resistance of the deposits was evaluated with a cavitation erosion jet adhering to ASTM G134 standard. Both Inconel 625 and SS 316 achieved better cavitation erosion resistance when compared to the base metal SS 316, with cold sprayed Inconel 625 having close to a four times improvement.